2010
DOI: 10.1080/09593331003621565
|View full text |Cite
|
Sign up to set email alerts
|

Reusable nanomaterial and plant biomass composites for the removal of Methylene Blue from water

Abstract: A novel composite has been prepared from nanomaterials and powdered orange peel. The composite is adhered to a plastic strip and may be employed for the removal of synthetic dyes from aqueous solutions, for example from dyehouse effluents. Using Methylene Blue (CI Basic Blue 9) as the reference dye, the characteristics of the adsorbent have been studied. The effect of pH, type of nanomaterial (e.g. carbon nanotubes, activated carbon nanotubes, or titanium dioxide nanoparticles), contact time, and reusability h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The values of K L and Q m obtained in our study are higher than those reported in the literature on the adsorption of MB onto metal oxide surface or low-cost adsorbents ( . Jain et al, 2010;Fangwen et al, 2009;Ofomaja, 2007;Mak and Chen, 2004;Dogan et al, 2004). It is possible that this because of the high surface area, good dispersion ability, and intrinsic reactivity of goethite nanoparticles.…”
Section: Nassar and Ringsredmentioning
confidence: 93%
“…The values of K L and Q m obtained in our study are higher than those reported in the literature on the adsorption of MB onto metal oxide surface or low-cost adsorbents ( . Jain et al, 2010;Fangwen et al, 2009;Ofomaja, 2007;Mak and Chen, 2004;Dogan et al, 2004). It is possible that this because of the high surface area, good dispersion ability, and intrinsic reactivity of goethite nanoparticles.…”
Section: Nassar and Ringsredmentioning
confidence: 93%
“…In this case, biomass, especially when porous or sponge-like, can be used as the ideal environment for the development of fungal mass, in view of the removal also of chlorinated compounds (Iqbal et al, 2005). Other possibilities are in absorbing dyes, such as Crystal Violet using peanut hulls (Tahir et al, 2017) and methylene blue using orange peel strips (Jain et al, 2010) from water.…”
Section: Other Possibilities For Reprocessing Biomass Wastementioning
confidence: 99%
“…• En el artículo "Compuestos de biomasa vegetal y nanomateriales reutilizables para la eliminación del azul de metileno del agua" 27 , se analizó varios materiales compuestos por nanopartículas y cáscara de naranja en polvo. Se utilizo para remover colorantes sintéticos de soluciones.…”
Section: Estado Del Arteunclassified